2012
DOI: 10.1126/science.1203601
|View full text |Cite
|
Sign up to set email alerts
|

Luminous Supernovae

Abstract: Supernovae, the luminous explosions of stars, have been observed since antiquity. However, various examples of superluminous supernovae (SLSNe; luminosities >7 × 10(43) ergs per second) have only recently been documented. From the accumulated evidence, SLSNe can be classified as radioactively powered (SLSN-R), hydrogen-rich (SLSN-II), and hydrogen-poor (SLSN-I, the most luminous class). The SLSN-II and SLSN-I classes are more common, whereas the SLSN-R class is better understood. The physical origins of the ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
419
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 557 publications
(432 citation statements)
references
References 81 publications
11
419
0
2
Order By: Relevance
“…Expanding upon this and a number of authors have suggested that magnetars may power superluminous type II and Ibc SNe (Thompson et al 2004;Woosley 2010;Kasen & Bildsten 2010;Gal-Yam 2012;Quimby et al 2011); indeed the 7.29 M progenitor model of Woosley (2010) is directly motivated by the presence of J1647-45 within Wd1. Moreover, Inserra et al (2013) studied the late-time lightcurves of five superluminous type Ic SNe, finding that the data are indeed consistent with these events being powered by the rapid spin-down of newly born magnetars (see also McCrum et al 2013;Nicholl et al 2013) Additionally, magnetars have also been proposed as the central engines of some gamma-ray bursts (GRBs; e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Expanding upon this and a number of authors have suggested that magnetars may power superluminous type II and Ibc SNe (Thompson et al 2004;Woosley 2010;Kasen & Bildsten 2010;Gal-Yam 2012;Quimby et al 2011); indeed the 7.29 M progenitor model of Woosley (2010) is directly motivated by the presence of J1647-45 within Wd1. Moreover, Inserra et al (2013) studied the late-time lightcurves of five superluminous type Ic SNe, finding that the data are indeed consistent with these events being powered by the rapid spin-down of newly born magnetars (see also McCrum et al 2013;Nicholl et al 2013) Additionally, magnetars have also been proposed as the central engines of some gamma-ray bursts (GRBs; e.g.…”
Section: Discussionmentioning
confidence: 99%
“…SLSNe are very luminous (M R < −21 mag) transients, probably arising from the explosion of very massive star (Quimby et al 2011;Gal-Yam 2012). In this case, it has been proposed that the first peak is powered by the post-shock cooling of extended stellar material (Nicholl et al 2015a;Piro 2015), whereas the main peak could be powered by a magnetar.…”
Section: Introductionmentioning
confidence: 99%
“…Supernovae are defined as superluminous (SLSN) when they reach M V < −21 Gal-Yam 2012). The most luminous SLSNe observed have M V ∼ −22.5 (Gal-Yam 2012).…”
Section: Superluminous Supernovaementioning
confidence: 99%